Respuesta :
11.8
Explanation: if we’re using PEMDAS then you have to do the exponent first which will turn the 3 to a 0. Then you multiply -2 times 0 which will equal 0. Next, you divide 23.6 and 2
Explanation: if we’re using PEMDAS then you have to do the exponent first which will turn the 3 to a 0. Then you multiply -2 times 0 which will equal 0. Next, you divide 23.6 and 2
Remember PEMDAS
Parentheses: none
Exponent:3 to the 0 power= 1 ( anything to the 0 power is 1)
Multiply:-2x1=-2
Divide:-2/2=-1
Add:none
Subtract:23.6-1= 22.6
Answer is 22.6
Parentheses: none
Exponent:3 to the 0 power= 1 ( anything to the 0 power is 1)
Multiply:-2x1=-2
Divide:-2/2=-1
Add:none
Subtract:23.6-1= 22.6
Answer is 22.6